2017
DOI: 10.1038/s41467-017-00439-1
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the nosiheptide indole side ring centers on a cryptic carrier protein NosJ

Abstract: Nosiheptide is a prototypal thiopeptide antibiotic, containing an indole side ring in addition to its thiopeptide-characteristic macrocylic scaffold. This indole ring is derived from 3-methyl-2-indolic acid (MIA), a product of the radical S-adenosylmethionine enzyme NosL, but how MIA is incorporated into nosiheptide biosynthesis remains to be investigated. Here we report functional dissection of a series of enzymes involved in nosiheptide biosynthesis. We show NosI activates MIA and transfers it to the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 58 publications
6
26
2
Order By: Relevance
“…More recently, the Zhang laboratory also showed that NosJ-MIA also serves as a substrate for NosN, which it converts to NosJ-DMIA. 6 …”
Section: Discussionmentioning
confidence: 99%
“…More recently, the Zhang laboratory also showed that NosJ-MIA also serves as a substrate for NosN, which it converts to NosJ-DMIA. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Unusually, NosL initiates this intricate transformation by abstracting an H-atom from the α-amino group, rather than a carbon centre [148][149][150][151] . The subsequent formation of the indolic side-ring system from MIA involves the action of a novel, discrete, indoyl thiolation protein that was previously unannotated (NosJ) and a unique α/β-hydrolase fold protein (NosK) that transfers the indoyl to a linear pentathiazolyl peptide intermediate Cys residue that remains selectively unmodified [152][153][154] (FIG. 9).…”
Section: Radical Sam Enzymesmentioning
confidence: 99%
“…NosN has been stated to produce 5′-deoxyadenosine (5′-dA) and either S-adenosylhomocysteine (SAH) or thioadenosine (tA), depending on whether S-adenosylmethionine (SAM) or methylthioadenosine (MTA) acts as a methyl donor, respectively (Ding, Li, et al, 2017; LaMattina et al, 2017). SAM typically degrades to MTA during long periods of storage, which is heavily dependent on the pH of the storage solution and the temperature.…”
Section: Quantitative Analysis Of Nosn Turnovermentioning
confidence: 99%
“…Biosynthesis of the side-ring begins with NosL, which catalyzes the C α –C β fragmentation–recombination of L-Trp to afford MIA (Bhandari, Fedoseyenko, & Begley, 2016; Sicoli et al, 2016; Zhang et al, 2011). AMP is then attached to the carboxyl group of MIA by NosI to allow for transfer of MIA to the 4′-phosphopantetheine prosthetic group on NosJ (Badding et al, 2017; Ding, Ji, et al, 2017; Qiu et al, 2017). NosJ then shuttles MIA to NosK, an α/β hydrolase that attaches MIA onto a seryl residue within its active site.…”
Section: Introductionmentioning
confidence: 99%